GD2 chimeric antigen receptor modified T cells in synergy with sub-toxic level of doxorubicin targeting osteosarcomas - Chulanetra, Monrat (Am J Cancer Res, 2020)
Since the prognosis for children with high-risk osteosarcoma (OS) remains suboptimal despite intensive multi-modality therapies, there is a clear and urgent need for the development of targeted therapeutics against these refractory malignancies. Chimeric antigen receptor (CAR) modified T cells can meet this need by utilizing the immune system’s potent cytotoxic mechanisms against tumor specific antigen targets with exquisite specificity. Since OS highly expresses the GD2 antigen, a viable immunotherapeutic target, we sought to assess if CAR modified T cells targeting GD2 could induce cytotoxicity against OS tumor cells. We demonstrated that the GD2 CAR modified T cells were highly efficacious for inducing OS tumor cell death. Interestingly, the OS cells were induced to up-regulate expression of PD-L1 upon interaction with GD2 CAR modified T cells, and the specific interaction induced CAR T cells to overexpress the exhaustion marker PD-1 along with increased CAR T cell apoptosis. To further potentiate CAR T cell killing activity against OS, we demonstrated that suboptimal chemotherapeutic treatment with doxorubicin can synergize with CAR T cells to effectively kill OS tumor cells.